2020
DOI: 10.1177/0269094220988852
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant entrepreneurs in rural England – An examination of the socio- cultural barriers facing migrant small businesses in Lincolnshire

Abstract: A growing body of literature recognises the crucial role played by immigrant entrepreneurs. However, certain socio-cultural barriers adversely affect their businesses in rural areas. Thus, this article examines the socio-cultural barriers facing immigrant entrepreneurs in Lincolnshire. Eleven semi-structured interviews were held with businesses owned by immigrants from diverse ethnic backgrounds. The findings identified migrant ethnocentrism, stereotypes, cultural differences and language differences as key so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…This suggests that overall, for these migrant mothers, isolation and powerlessness were more commonly experienced. This finding aligns with some studies that reported on migrant populations' experiences of alienation more generally, reporting that alienation was expressed by participants predominantly as feelings or experiences of isolation and powerlessness (Hack‐Polay et al, 2020; Pepanyan et al, 2019). Interestingly, normlessness was only reported by migrant mothers of children with a disability/disorder.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that overall, for these migrant mothers, isolation and powerlessness were more commonly experienced. This finding aligns with some studies that reported on migrant populations' experiences of alienation more generally, reporting that alienation was expressed by participants predominantly as feelings or experiences of isolation and powerlessness (Hack‐Polay et al, 2020; Pepanyan et al, 2019). Interestingly, normlessness was only reported by migrant mothers of children with a disability/disorder.…”
Section: Discussionsupporting
confidence: 89%
“…There is no gainsaying that language differences in the operating environment of the immigrant entrepreneur's small businesses is a major challenge (Hack-Polay, Ogbaburu, Rahman & Mahmoud, 2020). This according to Doole, Lowe and Kenyon (2016), is because language is a critical socio-cultural factor that affects marketing communications and so poor language competencies typically hinder business expansion.…”
Section: Social Capitalmentioning
confidence: 99%
“…It has been argued that success of SMEs is partly dependent on the skills of the owners and managers (Hack-Polay, Ogbaburu & Rahman, 2020;Bryan, 2006). International business skills assist firms in becoming successful in both local and international markets by developing business expertise, international orientation, environmental perceptions and demographic diversity (Manolova et at., 2002).…”
Section: Hypothesis Developmentmentioning
confidence: 99%